2012
DOI: 10.1016/j.npep.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset PYY overexpression in mice reduces food intake and increases lipogenic capacity

Abstract: Peptide YY (PYY) is best known for its important role in appetite regulation, but recent pharmacological studies have suggested that PYY is also involved in regulating energy balance and glucose homeostasis. However, the mechanism behind the regulation of these parameters by PYY is less clear. Here, by utilising an inducible transgenic mouse model where PYY overexpression is induced in adult animals (PYYtg) and release of mature PYY peptides is controlled by endogenous machineries, we show that elevating PYY l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Notably, in our previous study, the single-housed mice fed WPI had a reduced intestinal length and reduced ileal gene expression for PYY and FATP4 (26), whereas group-housed mice used in the current study only reduced FATP4 gene expression. Given the (contrasting) effects of PYY on anabolic and catabolic pathways (43), and the role played by FATP4 in intestinal lipid transport (2), the data suggest a potential interaction between the housing environment and whey proteins on intestinal morphology (length) and cellular activity linked to energy balance regulation. In fact, Tranberg et al showed that group-housed mice fed WPI as part of a 60% energy high-fat diet (HFD) also increased energy intake and reduced body weight gain, similar to the current study, but, in this instance, the effect was transient, only seen in the first week of diet intake (47).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, in our previous study, the single-housed mice fed WPI had a reduced intestinal length and reduced ileal gene expression for PYY and FATP4 (26), whereas group-housed mice used in the current study only reduced FATP4 gene expression. Given the (contrasting) effects of PYY on anabolic and catabolic pathways (43), and the role played by FATP4 in intestinal lipid transport (2), the data suggest a potential interaction between the housing environment and whey proteins on intestinal morphology (length) and cellular activity linked to energy balance regulation. In fact, Tranberg et al showed that group-housed mice fed WPI as part of a 60% energy high-fat diet (HFD) also increased energy intake and reduced body weight gain, similar to the current study, but, in this instance, the effect was transient, only seen in the first week of diet intake (47).…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, PYY and PP levels are known to increase in response to food intake and they can act as satiety factors on specific Y-receptors in the brain 13,16,17,54,55 . A local increase in PYY or PP in the pancreatic islet would therefore also be very timely to counter-regulate the increase of insulin secretion postprandial.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adrenaline, noradrenaline and peptide YY (PYY) have also been implicated in the inhibition of insulin release 1115 . PYY, a 36 amino acid peptide released from L-type cells of the gut and a member of the NPY family, is well recognised for its role to inhibit feeding and increase energy expenditure through activation of hypothalamic Y-receptors 13,16,17 . Importantly, however, PYY is also expressed in α-cells in the pancreatic islets where it is co-stored with glucagon in the secretory granules 18,19 , and its function in this tissue is less clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations